Diagnostic value of thyroid-related serological indicators and pan-immune-inflammation value for differentiated thyroid carcinoma - Yicheng Wen; Xin Yi; Jixin Shi; Peng Wan; Huan Wang; Li Tian; Huixia Liu (Frontiers in Immunology)
BackgroundOver the past decade, the remarkable rise in differentiated thyroid carcinoma (DTC) incidence, combined with the limitations of conventional diagnostic approaches, have prompted this study to explore the diagnostic value of thyroid-related serological indicators and pan-immune-inflammation value (PIV) for DTC, based on advancements in molecular biology and immunology.MethodsBased on postoperative pathological diagnosis, the present retrospective research comprised 112 individuals afflicted with DTC (observation group) and 93 individuals having benign thyroid tumors (control group) from January 2023 to January 2025. Differences in clinical data between the two groups were analyzed via univariate statistical methods. Logistic regression analyses identified influencing factors, while diagnostic value of thyroid-related serological indicators and PIV levels were evaluated through receiver operating characteristic analysis.ResultsIntergroup differences regarding the levels of thyroxine (T4), free thyroxine (FT4), thyroid-stimulating hormone (TSH), thyroglobulin (Tg), lymphocyte count, monocyte count, and PIV were found to be significant (p<0.05). Additionally, negative correlation of lymphocyte count with DTC was noted by univariate binary logistic regression (odds ratio [OR] = 0.243, 95% confidence interval [CI]: 0.143–0.411]). TSH (OR=2.458, 95% CI: 1.690–3.575), FT4 (OR=1.383, 95% CI: 1.205–1.588), Tg (OR=1.008, 95% CI: 1.001–1.015), and PIV (OR=1.003, 95% CI: 1.000–1.005) were identified as independent influencing factors for DTC, and the area under the curve for their combination was 0.860 (95% CI: 0.809–0.912, sensitivity: 86.2%, specificity: 77.2%).ConclusionThis retrospective study suggested that TSH, FT4, Tg, and PIV were positively correlated with DTC, and their combination yielded the best diagnostic performance. It highlighted the potential utility of PIV as a novel immune-inflammatory biomarker and provided support for the development of DTC diagnosis.